The Influence of Problem-Based Learning and Direct Teaching on Students’ Learning Outcomes - Heru Raharjo; M. Khairudin; Jamil Abd Baser (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
One of the student-centered learning methods which is able to improve the students’ learning outcomes is Problem-Based Learning (PBL). This study examined (1) the difference in the learning results of students using PBL and Direct Teaching (DT) with high and low learning motivation and creativity, (2) the influence of learning methods with motivation and creativity toward learning outcomes, and (3) the difference in the learning results of students using PBL and DT in terms of learning motivation and creativity. The subject consisted of students of Vocational High Schools or Sekolah Menengah Kejuruan N 1 Ngawen. The data analysis used an ANOVA test and a T-test. The results revealed (1) insignificantly different learning outcomes between the use of PBL and DT, (2) insignificantly different learning outcomes with the significance of 0.652 between students with high and low motivation, (3) significantly different learning outcomes with the significance of 0.039 between students with high and low creativity, (4) influence of the interaction between learning methods with learning motivation to the learning outcomes, (5) influence of the interaction between learning methods with creativity to the learning outcomes, (6) insignificantly different learning outcomes between students using PBL and DT in terms of learning motivation, and (7) insignificantly different learning outcomes between students using PBL and DT in terms of creativity.